Trustworthy Artificial Intelligence Implementation Introduction to the TAII Framework - Baker-Brunnbauer, Josef (Cham : Springer International Publishing : Imprint: Springer, 2023)
Rapidly developing Artificial Intelligence (AI) systems hold tremendous potential to change various domains and exert considerable influence on societies and organizations alike. More than merely a technical discipline, AI requires interaction between various professions. Based on the results of fundamental literature and empirical research, this book addresses the management's awareness of the ethical and moral aspects of AI. It seeks to fill a literature gap and offer the management guidance on tackling Trustworthy AI Implementation (TAII) while also considering ethical dependencies within the company. The TAII Framework introduced here pursues a holistic approach to identifying systemic ethical relationships within the company ecosystem and considers corporate values, business models, and common goods aspects like the Sustainable Development Goals and the Universal Declaration of Human Rights. Further, it provides guidance on the implementation of AI ethics in organisations without requiring a deeper background in philosophy and considers the social impacts outside of the software and data engineering setting. Depending on the respective legal context or area of application, the TAII Framework can be adapted and used with a range of regulations and ethical principles. This book can serve as a case study or self-review for c-level managers and students who are interested in this field. It also offers valuable guidelines and perspectives for policymakers looking to pursue an ethical approach to AI. .
1. Introduction -- 2. Artificial Intelligence -- 3. Ethics and Moral -- 4. Business and Management Perspective -- 5. Empirical Study -- 6. Findings -- 7. TAII Framework.
Keywords: Business information services; Business ethics; Technology -- Moral and ethical aspects; Industrial organization; Artificial intelligence; IT in Business; Business Ethics; Ethics of Technology; Organization; Artificial Intelligence